Peran Pendidikan Kewarganegaraan Dalam Membangun Kesadaran Identitas Nasional di Kalangan Remaja - Randi, Muhammad Sinar; Lestari, Anggun; Cantika, Nazla Ayu; Harahap, Siti Nurhidayah; Sihite, Rahmayani (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study examines the role of Civic Education (Pendidikan Kewarganegaraan - PKn) in fostering national identity awareness among teenagers. Utilizing a literature review methodology, this research compiles and analyzes findings from various Indonesian journals. The results indicate that effective PKn education, particularly when utilizing interactive teaching methods such as discussions, simulations, and group projects, significantly enhances students' understanding and appreciation of national values, history, and symbols. Despite these positive outcomes, the study identifies challenges such as inadequate resources and differing interpretations of national values across regions. It emphasizes the importance of competent educators and the integration of Pancasila values in the PKn curriculum. The study concludes that with proper support from the government, schools, and the community, PKn can effectively cultivate a strong national identity in the younger generation, preparing them to face global challenges while maintaining their national identity.